Theater and Psychological Development: Assessing Socio-Cognitive Complexity in the Domain of Theater. Issue 2 (3rd April 2017) - Silva, José Eduardo; Ferreira, Pedro; Coimbra, Joaquim Luís; Menezes, Isabel
Abstract : Theater is a millenary art form that has stably maintained its minimum indispensable elements over the years. Yet, not much is known about the psychological impact of this performing art. A literature review shows a broad and sometimes contradictory spectrum of theoretical and empirical evidence. In the last few decades, however, interdisciplinary studies, namely in the emerging field of neuroaesthetics, has allowed the emergence of new perspectives on the study of the arts. Drawing from these findings, and to better understand the impact of theater in the socio-cognitive development of actors, directors, and other practitioners, this study tested the construction of an instrument exploring complexity of thought in relation to theater. A preliminary study for the Scale of Socio-cognitive Complexity in the Domain of Theatre (SSCDT) showed that, among a sample of 222, individuals with higher levels of experience in acting and directing seem to demonstrate higher levels of cognitive complexity. To our knowledge, this was the first study aiming to develop a simple paper-and-pencil instrument capable of providing data about the psychological impact of theater in terms of socio-cognitive complexity.